An Overview of Inclusive Education in Eastern Aceh, Indonesia: What do the Educational Elements Say? - A. Muchsin, Misri; Pratiwi, Siti Habsari; Salasiyah, Cut Intan; Manan, Abdul; Kamarullah, Kamarullah (Jurnal Ilmiah Peuradeun, 2022)
Children with disabilities indeed are encouraged to have equal status in education with the normal ones. However, some domains may face particular challenges. Our article explores the insights of current inclusive education in eastern Aceh – Kabupaten Aceh Timur, Kabupaten Aceh Tamiang, and Kota Langsa – by discovering the views of 104 participants (students, teachers, principals, and officials of educational departments) on inclusive education. By applying a qualitative approach, we integrated a descriptive method through the distribution of questionnaires and interviews. Further, we analyzed the data in data reduction, display, and conclusion drawing stages. All students – both regular and disabled - had no problems sharing the same classroom, including the teachers and other school facilities, although some disabled thought that their school should have specific needs for them. Meanwhile, the officials had no strong power to support the development of inclusive education, while several schools may model inclusivity based on their school policy. Maximizing existing special education teachers, socializing the disabled’ needs to earn the rights for education within communities, and establishing special education centers at the university level, may contribute to the lack of inclusive education development in those regions.